Dairy Products: Is There an Impact on Promotion of Prostate Cancer? A Review of the Literature - Vasconcelos, Alexandra; Santos, Teresa; Ravasco, Paula; Neves, Pedro Miguel (Frontiers in Nutrition, 2019)
This review of the literature aims to study potential associations between high consumption of milk and/or dairy products and prostate cancer (PC). Literature is scarce, yet there is a direct relationship between mTORC1 activation and PC; several ingredients in milk/dairy products, when in high concentrations, increase signaling of the mTORC1 pathway. However, there are no studies showing an unequivocal relationship between milk products PC initiation and/or progression. Three different reviews were conducted with articles published in the last 5 years: M1) PC and intake of dairy products, taking into account the possible mTORC1signaling mechanism; M2) Intake of milk products and incidence/promotion of PC; M3) mTORC1 activation signaling pathway, levels of IGF-1 and PC; M4) mTORC pathway and dairy products. Of the 32 reviews identified, only 21 met the inclusion criteria and were analyzed. There is little scientific evidence that directly link the three factors: incidence/promotion of PC, intake of dairy products and PC, and PC and increased mTORC1 signaling. Persistent hyper-activation of mTORC1 is associated with PC promotion. The activity of exosomal mRNA in cellular communication may lead to different impacts of different types of milk and whether or not mammalian milks will have their own characteristics within each species. Based on this review of the literature, it is possible to establish a relationship between the consumption of milk products and the progression of PC; we also found a possible association with PC initiation, hence it is likely that the intake of dairy products should be reduced or minimized in mens’ diet.